Phillygenin exhibits anti-inflammatory activity through modulating multiple cellular behaviors of mouse lymphocytes. (2nd January 2019) - Du, Bingyuan; Zhang, Li; Sun, Ying; Zhang, Guimin; Yao, Jingchun; Jiang, Mingmin; Pan, Lihong; Sun, Chenghong
Abstract: Context: Phillygenin (PHI) is an intestinal metabolite of phillyrin from the genus Forsythia . Although the regulatory activity of Forsythia on immune system has been investigated, the effect of PHI on activated lymphocytes is poorly understood. Objective: This study was aimed to discuss the possible anti-inflammation potential of PHI on mitogen-activated stimulated lymphocytes in vitro . Methods: Mice spleen lymphocytes were incubated with PHI for 4 h, and then stimulated with concanavalin A (Con A) or phorbol 12-myristate 13-acetate/ionomycin (PMA + Ion). Cell viability was assayed by cell counting kit-8 (CCK-8). The expression of CD69 and CD25, proliferation, cell cycle, intracellular Ca 2+ concentration, apoptosis, mitochondrial inner membrane potential ( ΔΨm ), mitochondrial permeability transition (MPT), interleukin-2 (IL-2), interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α) were analyzed by flow cytometry. The expression of cyclin B1, cyclin D1, Cyclin E, and the phosphorylation of c-jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (Erk1/2) and p38 were assayed by western blotting. Results: The results showed that PHI inhibited the proliferation of Con A-activated lymphocytes and induced a G0 /G1 phase arrest by suppressing cyclin D1 and cyclin E. Meanwhile, PHI antagonized Con A-induced T cells activation through blocking intracellular Ca 2+ overload and suppressing the phosphorylation of JNK and Erk1/2. Both Con A and PMA + Ion-induced secretion of IL-2, IFN-γ, and TNF-α were attenuated by PHI. PHI enhanced Con A-induced lymphocytes apoptosis through decreasing ΔΨm and increasing MPT. Conclusion: These results suggest that PHI exhibits its anti-inflammatory activity through modulating multiple cellular behaviors, leading to the suppression of the adaptive immune response.